2018
DOI: 10.1002/pbc.27274
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to reducing admissions for children with sickle cell disease in pain crisis through individualization and standardization in the emergency department

Abstract: This study presents an effective strategy to reduce admission rate for children with SCD presenting with VOC. Shorter time to second opiate dosing was also associated with reduced risk of admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
(45 reference statements)
2
14
0
Order By: Relevance
“…5 Although this study did not show a reduction in admission rate with the use of individualized pain plans, other pediatric studies have. 6 The difference may be due to a difference in data collection periods FDR, False-discovery rate; DM, diabetes mellitus; VTE, venous thromboembolism; LWBS, left without being seen. *Estimate is the exponential of the coefficient estimated from the model.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although this study did not show a reduction in admission rate with the use of individualized pain plans, other pediatric studies have. 6 The difference may be due to a difference in data collection periods FDR, False-discovery rate; DM, diabetes mellitus; VTE, venous thromboembolism; LWBS, left without being seen. *Estimate is the exponential of the coefficient estimated from the model.…”
Section: Discussionmentioning
confidence: 99%
“…22,27 The enhanced recovery after surgery protocols have been shown to reduce perioperative opioids use, LOS, and perioperative morbidity. 12,13,30,31 In addition, patient education and written guidelines for surgeons have reduced the number of opioids prescribed after surgery. 3,8-10,32,33 Similarly, setting limits on prescription quantities has also had some success in decreasing opioid prescriptions postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Although opioid use history was considered, it did not substantially influence the pain control program. In other medical specialties, Schefft et al 31 demonstrated that the presence of an individualized pain plan reduced the admission rates for children with sickle cell disease presenting in vaso-occlusive crisis. Their individualized pain plan was built with consideration of the patient's opioid experiences from prior hospitalizations.…”
Section: Figurementioning
confidence: 99%
“…Research has suggested several approaches for reducing avoidable healthcare utilization in patients with SCD, such as the use of individual pain treatment plans when patients present to the ED with a VOC, and shorter time to opiate dosing [ 26 , 43 ]. Shifting care from the reactionary acute setting to proactive disease management provided in the clinic may also reduce avoidable utilization.…”
Section: Discussionmentioning
confidence: 99%